Pengaruh Kualitas Pelayanan dan Periklanan terhadap Keputusan Nasabah dalam Menabung pada Bank Syariah (Studi Kasus pada BTN Syariah Surakarta) - Haris, Helmi; T, Nur Said Irham (IAIN Salatiga, 2012)
This research aims to analyze the influence of service quality and advertisingpartially and simultaneously against the costumer decisions in saving moneyÂ at Bank Tabungan Negara (BTN) Syariah Surakarta. The population in thisÂ research are the total number of clients who save in Bank Tabungan NegaraÂ (BTN) Sharia Surakarta and using the Accidental Sampling as the methodÂ in sampling (numbers of sample are 98 respondent). The analysis tool thatÂ used in this research is â€œmultiple linear regressionâ€, which previously testedÂ the validity and realibility as well as the classic assumption test. Based onÂ the partial testing, both of service quality and advertising have significantÂ influence positively with the level of Ã¡ = 5% (0,05). The simultaneous testÂ showed that the influence of service quality and advertising is significantÂ with calculate F value 29.629 and the value of F table is 3.09